Taxonomías de la política exterior brasileña (2003-2014): ¿Sudamérica o Latinoamérica? - Moreira, Felipe Kern (El Colegio de México A.C., 2015)
The aim of this paper is to analyze South American integration as a formal priority of Brazilian foreign policy. It provides evidence to understand the goal of the Brazilian government, and sets out three criteria to assess the Brazilian priority of South American integration: cohesiveness of public policy, regional perception, and corporate structures in Latin America.